Implanted upper airway stimulation device for obstructive sleep apnea - Van de Heyning, Paul; Badr, M. Safwan; Maurer, Joachim T. (The laryngoscope, 2012)
Objectives/Hypothesis: Previous feasibility studies have shown that electrical stimulation of the hypoglossal nerve can improve obstructive sleep apnea (OSA). The current study examined the safety and preliminary effectiveness of a second generation device, the Upper Airway Stimulation (UAS) system, and identified baseline predictors for therapy success. Study Design: Two consecutive open prospective studies. Methods: UAS systems were implanted in patients with moderate to severe OSA who failed or were intolerant of continuous positive airway pressure (CPAP). The study was conducted in 2 parts. In part 1, patients were enrolled with broad selection criteria. Apnea hypopnea index (AHI) was collected using laboratory-based polysomnography at preimplant and postimplant visits. Epworth Sleepiness Scale (ESS) and Functional Outcomes of Sleep Questionnaire (FOSQ) were also collected. In part 2, patients were enrolled using selection criteria derived from the experience in part 1. Results: In part 1, 20 of 22 enrolled patients (two exited the study) were examined for factors predictive of therapy response. Responders had both a body mass index ≤32 and AHI ≤50 (P < .05) and did not have complete concentric palatal collapse. Part 2 patients (n = 8) were selected using responder criteria and showed an improvement on AHI from baseline, from 38.9 ± 9.8 to 10.0 ± 11.0 (P < .01) at 6 months postimplant. Both ESS and FOSQ improved significantly in part 1 and 2 subjects. Conclusions: The current study has demonstrated that therapy with upper airway stimulation is safe and efficacious in a select group of patients with moderate to severe OSA who cannot or will not use CPAP as primary treatment. Laryngoscope, 2012
Gesehen am 19.02.2019